2017
DOI: 10.4103/phrev.phrev_48_16
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding of antiobesity property of capsaicin

Abstract: The capsaicin is an ingredient that we normally mix in food in many cultural cuisines even in fresh and dried production. Because of its anticancer, anticholesterolemic, antidiabetic, antihypertensive, anti-inflammatory, antimicrobial, and antioxidant properties, capsaicin is used worldwide. Moreover, capsaicin is also used for the protection of cardiovascular and hepatic diseases. The electronic databases PubMed, Scopus, Web of Science, Google Scholar, and ScienceDirect were searched since 2000 to present for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Capsaicin consumption 1 hr before low intensity exercise is a valuable supplement for individuals with hyperlipidemia and/or obesity since it improves lipolysis. In humans, capsaicinoid ingestion increases energy expenditure through the activation of brown adipose tissue (Georgescu et al, 2017;Leung, 2014;Narang, Jiraungkoorskul, & Jamrus, 2017). Besides, Marrelli, Menichini, and Conforti (2016) found that hot pepper (C. annuum) flower extract inhibited (IC 50 3.54 ± 0.18 mg/mL) the activity of pancreatic lipase, key enzyme for triglycerides absorption in the small intestine.…”
Section: Antiobesity Effectmentioning
confidence: 99%
“…Capsaicin consumption 1 hr before low intensity exercise is a valuable supplement for individuals with hyperlipidemia and/or obesity since it improves lipolysis. In humans, capsaicinoid ingestion increases energy expenditure through the activation of brown adipose tissue (Georgescu et al, 2017;Leung, 2014;Narang, Jiraungkoorskul, & Jamrus, 2017). Besides, Marrelli, Menichini, and Conforti (2016) found that hot pepper (C. annuum) flower extract inhibited (IC 50 3.54 ± 0.18 mg/mL) the activity of pancreatic lipase, key enzyme for triglycerides absorption in the small intestine.…”
Section: Antiobesity Effectmentioning
confidence: 99%
“…Dietary capsaicin has also been shown to alleviate metabolic dysregulation in diabetic obese mice, thus exhibiting anti-obesity properties ( 193 ). Several mechanisms in this regard have been explored ( 194 ). Capsaicin has satiety-inducing properties and suppresses appetite ( 195 ).…”
Section: Bioactives and Osteoarthritis: Metabolic And Anti-inflammato...mentioning
confidence: 99%
“…Through the ages, Capsicum fruits have been consumed widely for their appealing taste as well as medicinal benefits, such as in the treatment of asthma, toothaches, cough, fever, gastrointestinal disorders, skin problems, diabetic neuropathy, and postherpetic neuralgia. 2−4 In the last two decades, capsaicin and its derivatives have also been explored for their biological and physiological functions, such as metabolism stimulants; antiobesity, 5 anti-inflammatory, 6 and anticancer 7 medications; antioxidants; 8 and analgesics 9 in pharmacological formulations and application. 10 Carotenoids and anthocyanins on the other hand are not only utilized as natural colorants and food additives but also have high antioxidative, anti-inflammatory, antiaging, and skin-and eye-care properties associated with them.…”
Section: Introductionmentioning
confidence: 99%
“…The biochemical composition of Capsicum is beneficial not only for plant survival and defense but also for human consumption and health. Through the ages, Capsicum fruits have been consumed widely for their appealing taste as well as medicinal benefits, such as in the treatment of asthma, toothaches, cough, fever, gastrointestinal disorders, skin problems, diabetic neuropathy, and postherpetic neuralgia. In the last two decades, capsaicin and its derivatives have also been explored for their biological and physiological functions, such as metabolism stimulants; antiobesity, anti-inflammatory, and anticancer medications; antioxidants; and analgesics in pharmacological formulations and application . Carotenoids and anthocyanins on the other hand are not only utilized as natural colorants and food additives but also have high antioxidative, anti-inflammatory, antiaging, and skin- and eye-care properties associated with them. The industrial use of Capsicum as dried paprika powder or in the form of oleoresin, which is a concentrated extract of capsaicinoids, flavonoids, carotenoids, and polyphenols obtained from the Capsicum fruits, finds application in food, cosmetics, as well as military purposes …”
Section: Introductionmentioning
confidence: 99%